FIRST DESCRIPTION ON MOLECULAR CHARACTERISATION OF HEMIURID TREMATODE Lecithocladium excisum FROM BLOCH,1795: Apolectus niger (PISCES: CARANGIDAE:) USING 18S RIBOSOMAL DNA MARKER - SINGH, RATNESH KUMAR; SAXENA, A. M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2022)
A total of 55 specimens of Bloch: Apolectus niger (Pisces: Carangidae) were obtained during the current inquiry from the sea beach of Puri, Orissa, India. It is a commercially significant marine fish, since it is a highly valued source of nutrition for human consumption. One type of the digenetic trematodes was collected from the gut of the affected fish, which belong to the genus, Lecithocladium, of the family Hemiuridae. Partial nucleotide sequences of the 18S ribosomal gene were acquired from this trematode species and deposited in the GenBank. Molecular analysis of the parasites using 18s small subunit rDNA was undertaken to evaluate their phylogenetic position with respect to previously known species in GenBank, which strikingly confirmed their molecular phylogeny revealed here. The hemiurid species from the genus, Lecithocladium are found to be L. excisum. A comparison of 18S rDNA sequences indicated that they exhibited 98.0 percent sequence similarity with Dinurus longisinus.